Repurposing drugs with specific activity against L-form bacteria - Emami, Kaveh; Banks, Peter; Wu, Ling Juan; Errington, Jeffery (Frontiers in Microbiology, 2023)
Cell wall deficient “L- form” bacteria are of growing medical interest as a possible source of recurrent or persistent infection, largely because of their complete resistance to cell wall active antibiotics such as β-lactams. Antibiotics that specifically kill L-forms would be of potential interest as therapeutics, but also as reagents with which to explore the role of L-forms in models of recurrent infection. To look for specific anti-L-form antibiotics, we screened a library of several hundred FDA-approved drugs and identified compounds highly selective for L-form killing. Among the compounds identified were representatives of two different classes of calcium channel blockers: dihydropyridines, e.g. manidipine; and diphenylmethylpiperazines, e.g. flunarizine. Mode of action studies suggested that both classes of compound work by decreasing membrane fluidity. This leads to a previously recognised phenotype of L-forms in which the cells can continue to enlarge but fail to divide. We identified a considerable degree of variation in the activity of different representatives of the two classes of compounds, suggesting that it may be possible to modify them for use as drugs for L-form-dependent infections.